Synthesis of 2-Hidroxyethyl Ester (2-HEE) and 2-Hydroxypropyl Ester (2-HPE) from Castor Oil as Bioadditives to Improve the Cold Flow Characteristic of Biodiesel - Yulfi Zetra; Nirmala Puteri Batari; Talitha Fitra Firdausya; Yunita Alfiyati Firdausa; Rizka Berliana Putri; R.Y. Perry Burhan; Yuly Kusumawati (Automotive Experiences, 2026)
The utilization of biodiesel continues to increase along with the development of renewable energy. However, biodiesel tends to exhibit poorer cold flow properties compared to petroleum diesel. In this study, castor oil, a non-edible vegetable oil, was modified into 2-hydroxyethyl ester (2-HEE) and 2-hydroxypropyl ester (2-HPE) to improve the cold flow characteristic of biodiesel. The transesterification of 2-HEE and 2-HPE was carried out using fatty acid methyl esters (FAME) derived from castor oil with ethylene glycol (for 2-HEE) and propylene glycol (for 2-HPE), assisted by a K₂CO₃ catalyst at 150 °C, a mixing speed at 500 rpm, under a vacuum system. The optimum molar ratio of FAME to polyol was 1:10, yielding 69.63% for 2-HEE and 56.84% for 2-HPE. GC–MS analysis showed product abundances of 98.17% for 2-HEE (dominated by 2-hydroxyethyl ricinoleate at 77.4%) and 98.97% for 2-HPE (dominated by 2-hydroxypropyl ricinoleate at 77.9%). The addition of 2% v/v 2-HEE to biodiesel reduced the cloud point by 2.2 °C, the pour point by 3 °C, the flash point by 3 °C, and the density by 0.005 g/cm³, while increasing the kinematic viscosity by 0.21 cSt. Meanwhile, the addition of 2% v/v 2-HPE reduced the cloud point by 3.1 °C, the pour point by 4.3 °C, the flash point by 8 °C, and the density by 0.001 g/cm³, with an increase in kinematic viscosity of only 0.01 cSt. The 2-HPE compound showed superior performance as a bioadditive compared to 2-HEE in improving the cold flow characteristic of biodiesel without significantly altering its physical properties.